Amino acid-catalyzed formation of 2-vinylfuran from lipid-derived 4-oxo-2-hexenal. (1st December 2015) - Zeng, Zhen; Ma, Jimei; Liu, Bin; Jiang, Hong
Highlights: 2-Vinylfuran was formed by the degradation of 4-oxo-2-hexenal. Amino acids promoted OHE degradation. Higher temperature was conducive to the formation of 2-vinylfuran. Abstract: The formation of 2-vinylfuran from the corresponding 4-oxo-2-hexenal (OHE, a lipid oxidation product) under the catalysis of amino acid were studied. The effects of amino acids, reaction temperature, reaction time, water content, pH, metallic ions and some food additives on the formation of 2-vinylfuran were investigated. Amino acids promoted the formation of 2-vinylfuran except aspartic acid, histidine and glutamine. Cysteine showed the strongest catalytic activity among the amino acids tested. Further investigation indicated that the intermediate 1-(furan-2-yl)ethanol played an very important role in the formation of 2-vinylfuran. Both higher temperature and acidic condition favored the transformation of OHE into 2-vinylfuran. The reaction time, water content, metallic ions and food additives also influenced the reaction to certain extent.